Long-cavity all-fiber ring laser actively mode locked with an in-fiber bandpass acousto-optic modulator - Cuadrado Laborde, Christian Ariel (2014)
We demonstrate low-frequency active mode locking of an erbium-doped all-fiber ring laser. As the mode locker, we used a new in-fiber bandpass acousto-optic modulator showing 74% modulation depth, 3.7 dB power insertion losses, 4.5 nm of optical bandwidth, and 20 dB of nonresonant light suppression. The laser generates 330 ps mode-locked pulses over a 10 ns pedestal, at a 1.538 MHz frequency, with 130 mW of pump power.